MELANESIA FOOD SECURITY STUDIES: A SYSTEMATIC LITERATURE REVIEW - Devi Mahdatul Ain; Salahudin Salahudin (Universitas Potensi Utama, 2023)
ABSTRACTThis study aims to examine more deeply the importance of food safety for the Melanesian race, the research method used in this study is systematic literature review which uses 150 scientific articles sourced from the Scopus database of article reviews using the Vosviewer application. The results of the study reveal that the occurrence of food security in Melanesians, namely trend diffusion, the results of this study contribute to the development and development of science, especially in terms of international relations that are relevant to issues of food security, in some countries where there is a Melanesian race such as Fiji, Papua, New Guinea as well as the Solomon Islands, security and the impact that occurs if there is an issue of food security. The limitations of this research are used articles which are only sourced from the Scopus database because the research results cannot fully describe and reflect issues that can be understood about Melanesian security itself. Therefore the article does not have comparative data, further research peril uses scientific articles sourced from other international databases, such as Web of science and Dimensions scholars.Â Keywords:Â Melanesia, food security, security, fiji, Solomon islands, trend diffusion